Liquidated : an ethnography of Wall Street - Ho, Karen Zouwen, 1971- (e-Duke books scholarly collection., 2009)
Financial collapses - whether of the junk bond market, the Internet bubble, or the highly leveraged housing market - are often explained as the inevitable result of market cycles: What goes up must come down. In Liquidated, Karen Ho punctures the aura of the abstract, all-powerful market to show how financial markets, and particularly booms and busts, are constructed. Through an in-depth investigation into the everyday experiences and ideologies of Wall Street investment bankers, Ho describes how a financially dominant but highly unstable market system is understood, justified, and produced through the restructuring of corporations and the larger economy. Ho, who worked at an investment bank herself, argues that bankers' approaches to financial markets and corporate America are inseparable from the structures and strategies of their workplaces. Her ethnographic analysis of those workplaces is filled with the voices of stressed first-year associates, overworked and alienated analysts, undergraduates eager to be hired, and seasoned managing directors.